Digital empowerment of women in the South African public sector - Shava, Elvin; Muringa, Tigere Paidamoyo (Frontiers in Sociology, 2025)
IntroductionThe digital empowerment of women in the South African public sector presents a strategic opportunity to enhance women’s technical competencies and boost their confidence in digital environments. Despite global progress, the inclusion of women in digital technologies and information communication technologies (ICTs) in South Africa remains low, reflecting persistent gendered marginalisation in the digital economy.MethodsThis study employed a systematic literature review methodology to investigate the challenges and opportunities surrounding women’s digital empowerment in the public sector of South Africa. Scholarly databases and search engines, including Google Scholar, Web of Science, and ScienceDirect, were used to retrieve and analyse peer-reviewed publications and relevant grey literature.ResultsThe findings highlight significant digital disparities that hinder the empowerment of women in the public sector. Key barriers include limited access to technical skills training, insufficient funding, a lack of targeted skills development workshops, organisational resistance to change, and broader issues of data marginalisation. These factors collectively undermine women’s participation in the digital transformation of public service.ConclusionThe study emphasises the urgent need for government-led initiatives to address the digital skills gap among women in the public sector. Strategic coproduction between government and stakeholders is essential to ensure inclusive and sustainable digital empowerment programmes. This research adds to the body of knowledge on digital democracy, innovation, and the empowerment of marginalised groups within public sector transformation efforts.